HALAL MANAGEMENT OF THE PLTD APUNG TSUNAMI PARK OF ACEH, INDONESIA: A LEGAL ANALYSIS - Muhammad Hafidh Sufli; Intan Qurratulaini; Safira Mustaqilla (JURISTA: Jurnal Hukum dan Keadilan, 2024)
This article aims to analyze the suitability of the management of Kapal PLTD Apung as a halal tourist attraction with the principles contained in Milk al-Daulah and Qanun Number 3 of 2022 concerning the Implementation of Halal Tourism in Banda Aceh city. This research uses a qualitative approach with descriptive analysis methods, as well as an empirical juridical approach to evaluate the implementation of halal tourism policies in the field. The research results show that although there have been efforts to adapt the management of Kapal PLTD Apung to halal tourism standards, there are still several challenges, such as physical damage, lack of innovation, lack of accessibility for people with disabilities, lack of halal certification for food and drinks, and lack of facilities. which makes it easier for visitors to access information. However, the management of Kapal PLTD Apung in most aspects reflects sharia values ​​and has great potential to contribute to the development of better and more sustainable halal tourism in Banda Aceh city.